Promotion, prevention, municipalization and health assurance in seven municipalities (2002)
Under the assumption that the State's basic administrative entity at local level is the municipality, a case study was carried out to identify potential relationships between health promotion and prevention, according to the Basic Attention Plan and the Compulsory Health Plan, and the processes of municipalization and health assurance. Municipalization of health was defined as being the ability to undertake competency and responsibility at the local level, and decentralization as being the certification that a municipality complies with all national requirements for such purpose. Three certified and four non-certified municipalities were studied, and their degrees of development of municipalization and their coverage of health assurance were analyzed. Greater developments in health promotion and prevention are related to greater developments in decentralization, independently of municipality decentralization. The most important advance in the health assurance process is the municipality's responsibility to affiliate its population to the subsidized regime.